2017
DOI: 10.1038/onc.2016.500
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ engages MEK/ERK to differentially regulate benign and malignant pancreas cell function

Abstract: While TGFβ signals are anti-proliferative in benign and well-differentiated pancreatic cells, TGFβ appears to promote the progression of advanced cancers. To better understand dysregulation of the TGFβ pathway, we first generated mouse models of neoplastic disease with TGFβ receptor deficiencies. These models displayed reduced levels of pERK irrespective of KRAS mutation. Furthermore, exogenous TGFβ led to rapid and sustained TGFBR1-dependent ERK phosphorylation in benign pancreatic duct cells. Similar to resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 39 publications
3
73
0
Order By: Relevance
“…The EGFR ligands such as TGF‐α may activate downstream AKT/ERK pathways by activating EGFR . Integrin β1 driven Src‐Akt hyperactivation can trigger EGFR ligand‐independent signaling . Besides, TGF‐β can activate downstream PI3K/AKT and p‐ERK by phosphorylating FAK .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EGFR ligands such as TGF‐α may activate downstream AKT/ERK pathways by activating EGFR . Integrin β1 driven Src‐Akt hyperactivation can trigger EGFR ligand‐independent signaling . Besides, TGF‐β can activate downstream PI3K/AKT and p‐ERK by phosphorylating FAK .…”
Section: Discussionmentioning
confidence: 99%
“…(30,31) Integrin b1 driven Src-Akt hyperactivation can trigger EGFR ligand-independent signaling. (32,33) Besides, TGF-b can activate downstream PI3K/AKT and p-ERK by phosphorylating FAK. (34,35) Conversely, when the activity of MMP is inhibited, this MMP-induced cleavage of the ligands is blocked, resulting in downregulation of the activity of AKT/ ERK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Since low expression of RasGRP1 in tTregs requires TGF‐β signaling, the data illustrate that TGF‐β acts as a survival factor in tTregs to resist PICA. Previous work by others demonstrated that TGF‐β signaling enhances the ERK signaling pathway by SMAD‐dependent and ‐independent manners in nonlymphoid cells . Our finding is therefore unique in that TGF‐β signaling suppresses RasGRP1 expression in T cells, which subsequently reduces ERK signaling.…”
Section: Resultsmentioning
confidence: 49%
“…Although we have shown a general modulation of the ERK-MAPK signaling pathway by miR-181a, the exact signaling events involved in miR-181a modulation of ERK-MAPK signaling in mo-DCs should be explored in a future study. Our data suggest that this might likely involve DUSP proteins; however, interactions with other identified molecules (Table S2), such as TGFBR2, CRK, and RASA2 (Principe et al, 2017), might also be relevant.…”
Section: Discussionmentioning
confidence: 85%